Seaweed on the egg hatching of Meloidogyne incognita and as a biostimulant in basil - Romero-Bastidas, Mirella; Rojas-Contreras, Maurilia; Arce- Amézquita, Pablo Misael; Rangel-Dávalos, Carlos; Guevara- Franco, José Alfredo; Hernández-Rubio, José Saúl (Ecosistemas y Recursos Agropecuarios, 2022)
Marine macroalgae in the control of the root-knot nematode emerges as a biological alternative to reduce the damage they cause in economically important crops such as basil. The objective of this study was to evaluate the effect of four macroalgae on the control of Meloidogyne incognita and on the growth of basil. For this, four extracts derived from Ulva lactuca, Ulva clathrata, Gracilaria spp. and Sargassum spp. were evaluated at three doses (1 000, 2 000 and 3 000 ppm) on the hatching of eggs and their effectiveness in germination, stem length and root of seedlings. In addition, a phytochemical analysis of the macroalgae that presented nematicidal action on the eggs was carried out. The results showed that the extract of Sargassum spp. and U. lactuca under the three doses evaluated generated the lowest number of hatched eggs. However, none macroalgae increased the germination percentage but the stem length did. In the phytochemical analysis, the extract of Sargassum spp. recorded the highest content of alkaloids, phenols, phytosterols, peptides and saponins. This research proves the efficacy of some marine macroalgae on the control of M. incognita and its biostimulant action on the plant, which is of great interest for organic and conventional agriculture.
Keywords: Growth, management, root-knot nematode, seaweed